Service Quality, Consumer Perception, Brand Awareness, and Consumer Satisfaction on Instagram - Rahayu, Rika; Yahya, Dian Ratnasari (Eksis: Jurnal Riset Ekonomi dan Bisnis, 2019)
This study aims to test and improve the service quality to customer satisfaction and brand awareness as an intervening variable when using Instagram social media. This research carries out quantitative methods using survey through questionnaires with a total sample of 137 respondents. To find out the responses of respondents to customer satisfaction when using Instagram social media in purchasing cosmetic products by using a Likert scale. Partial Least Square (PLS) is used in this research as the data processing. The results reveal that there was a significant relationship between service quality, consumer awareness, and brand awareness. Insignificant influence only causes brand awareness of consumer satisfaction, which causes customers to have difficulty in using Instagram social media the data is better than previous experience and the services provide sellers compared to paying attention to certain brand awareness.